Cubosomal lipid formulation of nitroalkene fatty acids: Preparation, stability and biological effects - Zatloukalová, Martina; Jedinák, Lukáš; Riman, Daniel; Franková, Jana; Novák, David; Cytryniak, Adrianna; Nazaruk, Ewa; Bilewicz, Renata; Vrba, Jiří; Papoušková, Barbora; Kabeláč, Martin; Vacek, Jan (Redox biology, 2021)
Lipid nitroalkenes - nitro-fatty acids (NO2-FAs) are formed in vivo via the interaction of reactive nitrogen species with unsaturated fatty acids. The resulting electrophilic NO2-FAs play an important role in redox homeostasis and cellular stress response. This study investigated the physicochemical properties and reactivity of two NO2-FAs: 9/10-nitrooleic acid (1) and its newly prepared 1-monoacyl ester, (E)-2,3-hydroxypropyl 9/10-nitrooctadec-9-enoate (2), both synthesized by a direct radical nitration approach. Compounds 1 and 2 were investigated in an aqueous medium and after incorporation into lipid nanoparticles prepared from 1-monoolein, cubosomes 1@CUB and 2@CUB. Using an electrochemical analysis and LC-MS, free 1 and 2 were found to be unstable under acidic conditions, and their degradation occurred in an aqueous environment within a few minutes or hours. This degradation was associated with the production of the NO radical, as confirmed by fluorescence assay. In contrast, preparations 1@CUB and 2@CUB exhibited a significant increase in the stability of the loaded 1 and 2 up to several days to weeks. In addition to experimental data, density functional theory-based calculation results on the electronic structure and structural variability (open and closed configuration) of 1 and 2 were obtained. Finally, experiments with a human HaCaT keratinocyte cell line demonstrated the ability of 1@CUB and 2@CUB to penetrate through the cytoplasmic membrane and modulate cellular pathways, which was exemplified by the Keap1 protein level monitoring. Free 1 and 2 and the cubosomes prepared from them showed cytotoxic effect on HaCaT cells with IC50 values ranging from 1 to 8 μM after 24 h. The further development of cubosomal preparations with embedded electrophilic NO2-FAs may not only contribute to the field of fundamental research, but also to their application using an optimized lipid delivery vehicle.
Keywords: Cubosome; Fatty Acids; KEAP-1; mastné kyseliny; Nitric oxide; Keratinocytes; Humans; Kelch-Like ECH-Associated Protein 1; oxid dusnatý; Nitro Compounds; dusíkaté sloučeniny; Monoacyl glycerol; Lipidic mesophase; Nitrooleate; NF-E2-Related Factor 2; lidé; faktor 2 související s NF-E2; Nitric Oxide